Agreement between the South Asia Foundation and BRAC University (2003) - South Asia Foundation; BRAC University (South Asia Foundation and BRAC University, 2013)
In conformity with the decisions regarding SAF Learning Initiative (hereinafter referred to as SAFLI) taken by the Vice-Chancellors/Rectors of Open Universities and Representatives of other distance education Institutions and Universities in the SAARC countries and approved by the Chairpersons of SAF Chapters at a meeting held on 19th February 2003, in Colombo, Srilanka, (hereinafter referred to as "Colombo Resolutions"), SAF and the BIL wish to enter into this agreement in regard to the design and implementation of SAFLI for the purpose of jointly delivering with other Institutions of distance education and Universities a Post-Graduate Diploma in Environment and Sustainable Development (PGD-ESD ), together with optional IT courses for students to choose from for added credits.